2012
DOI: 10.1021/np300248w
|View full text |Cite
|
Sign up to set email alerts
|

Case Study of Empirical and Computational Chemical Shift Analyses: Reassignment of the Relative Configuration of Phomopsichalasin to That of Diaporthichalasin

Abstract: Phomopsichalasin was isolated and assigned structure 1 over 15 years ago. Analysis of its proton NMR data led us to hypothesize that not all aspects of the relative configuration of this structure were correct. We have used both empirical and computational methods to propose an alternative structure. Diaporthichalasin was reported several years ago, and its structure was assigned as 7, a diastereomer of structure 1, and confirmed by a single crystal X-ray study. We have shown that diaporthichalasin and phomops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 16 publications
(32 reference statements)
3
26
0
Order By: Relevance
“…The CS values for 1 were also analyzed using both mean absolute error calculations and DP4 probability statistics. [7] The computation work supports the published relative configuration of C28–C29 of 1 in the anti conformation, which has the lowest TAD value at 2.89.…”
supporting
confidence: 80%
See 2 more Smart Citations
“…The CS values for 1 were also analyzed using both mean absolute error calculations and DP4 probability statistics. [7] The computation work supports the published relative configuration of C28–C29 of 1 in the anti conformation, which has the lowest TAD value at 2.89.…”
supporting
confidence: 80%
“…Thet otal absolute deviation (TAD) was used for the comparison of the absolute value of the difference between the calculated and the experimental values.T he CS values for 1 were also analyzed using both mean absolute error calculations and DP4 probability statistics. [7] Thec omputation work supports the published relative configuration of C28-C29 of 1 in the anti conformation, which has the lowest TADv alue at 2.89.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…These include (i) the use of only the global minimum from a molecular mechanics conformational search to proceed with the more computationally intensive ab initio phases of the calculations 5,27 , (ii) the use of a judiciously chosen small subset of structures from the conformer library generated in a molecular mechanics search 28,29 or (iii) the use of a judiciously chosen substructure (e.g., through truncation) as a model for the chemical shifts in question in the structurally ambiguous portion of the molecule (e.g., 3, Box 1 and 11, Fig. 3) 26,27 . A final caveat should be emphasized.…”
Section: Practical Considerationsmentioning
confidence: 99%
“…Table 4 footnote). The MAEs observed for hydrogen chemical shift are inherently smaller than carbon, and are generally considered to provide better distinction between isomer [45]. Interestingly, use of the DP4 method after assignment still indicated that carbon and proton data were in disagreement about the candidate structure corresponding to diastereomer 2b.…”
Section: Resultsmentioning
confidence: 99%